2002
DOI: 10.1046/j.1365-2958.2002.02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of phage‐resistance genes in temperate lactococcal bacteriophages

Abstract: Summary The sie2009 gene, which is situated between the genes encoding the repressor and integrase, on the lysogeny module of the temperate lactococcal bacteriophage Tuc2009, was shown to mediate a phage‐resistance phenotype in Lactococcus lactis against a number of bacteriophages. The Sie2009 protein is associated with the cell membrane and its expression leaves phage adsorption, transfection and plasmid transformation unaffected, but interferes with plasmid transduction, as well as phage replication. These o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 72 publications
(56 reference statements)
5
95
0
Order By: Relevance
“…The sie gene is actually the most prominent transcript from the Sfi21 prophage (54). A sie function is not excluded for ORF 22 by the Clostridium link, since the predicted protein showed two membrane-spanning domains, which concurs with the data reported for the sie functions in lactococcal phages encoded at a corresponding genome position (44). ORF 19 without a database match is located between phage lysin and integrase genes.…”
Section: Resultssupporting
confidence: 77%
“…The sie gene is actually the most prominent transcript from the Sfi21 prophage (54). A sie function is not excluded for ORF 22 by the Clostridium link, since the predicted protein showed two membrane-spanning domains, which concurs with the data reported for the sie functions in lactococcal phages encoded at a corresponding genome position (44). ORF 19 without a database match is located between phage lysin and integrase genes.…”
Section: Resultssupporting
confidence: 77%
“…Phage infection can be prevented in Gram-positive bacteria as a result of adsorption inhibition (Chatterjee, 1969;Tran et al, 1999;Wilkinson & Holmes, 1979), restriction modification systems (Kong & Josephsen, 2002), DNA injectionblocking systems (McGrath et al, 2002), lysogenization (Beard-Pegler & Vickery, 1985) and abortive infection systems (Dai et al, 2001). We showed that the in vitro VISA investigated demonstrated minimal to no alteration in SmaI RFLPs compared with parent strains; however, alterations in phage types were common.…”
Section: Resultsmentioning
confidence: 99%
“…It was speculated that the pNP40-encoded protein product might have an impact on the activity, production, or membrane insertion of Pip, thereby affect its biological function and prevent phage DNA entry [29]. The first description of a sie system of Lactococcus was published in 2002 and referred to the P335-type temperate lactococcal bacteriophage Tuc2009 [30]. After integration of the bacteriophage Tuc2009 genome into the lactococcal chromosome, the prophage protein Sie2009 is produced and blocks superinfecting phage DNA entry into the cell.…”
Section: Blocking Of Phage Dna Injectionmentioning
confidence: 99%
“…The effect of Sie2009 seems to be analogous to the effect of the lysogenic phage repressor (CI) preventing re-infection. In contrast, the presence of the sie2009 gene determines resistance to various phages, also to phages from other species [28,30]. Similarly to lactococci, in lactobacilli prophages are also a common phenomenon [31].…”
Section: Blocking Of Phage Dna Injectionmentioning
confidence: 99%
See 1 more Smart Citation